Prototipo para la enseñanza de los conversores estáticos de potencia (2004)
In this article the design of a didactic module is presented for the teaching of the Power electronics,where different applications of staticpower converters can be implemented, such as: AC voltage controllers (single phase and three phase), controlled rectifiers (single phase and three phase),choppers and bridges inverters (single phase and three phase). The device has an over load protection which avoid semiconductor damage in case 01 an incorrect or bad operation. Themodule can be programmed and controlled in local way using a keyboard and display or inremote wayfrom a PC by an application of Lab view. The developed prototype, at low cost, it is constituted in a tool that allows to the students to observe, using an oscilloscope, the differentwave forms obtained in the different converters; increasing their interest and facilitating the conceptualization of the different applications of the converters.